The moderating roles of ownership concentration and foreign ownership on enterprise risk management and firm performance / Zhang Lan Jun - Zhang , Lan Jun (2021)
This study examines the relationship between enterprise risk management, firm performance, and the moderating role of ownership concentration and foreign ownership on the relationship between enterprise risk management and enterprise performance. The study uses 6015 listed firms in the Shanghai Stock Exchange (SSE) and the Shenzhen Stock Exchange (SZSE) from 2016 to 2018. The results indicate that enterprise risk management significantly influences both short-term and long-term firm performance based on multiple regression and panel data analysis. The study also found that ownership concentration positively moderates the relationship between enterprise risk management and both short-term and long-term firm performance. However, foreign ownership is found to moderate the relationship between enterprise risk management only for long-term performance but has no significant effect on short-term performance. The results indicate that firms are advised to implement enterprise risk management to gain a competitive advantage and superior performance. At the same time, paying more attention to ownership concentration and foreign ownership is required.